1983
DOI: 10.1084/jem.157.3.907
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody against human T cell leukemia virus p19 defines a human thymic epithelial antigen acquired during ontogeny.

Abstract: Using monoclonal antibody 12/1-2 against a 19,000-dalton human T cell leukemia virus (HTLV) protein (anti-p19), previously demonstrated to be reactive with HTLV-infected human cells, but not in numerous other uninfected cells, we found a reactive antigen to be expressed on the neuroendocrine component of human thymic epithelial cells but not on any other normal epithelial or neuroendocrine human tissues. Moreover, this reactive antigen is acquired on neuroendocrine thymic epithelium during thymic ontogeny--fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 26 publications
(33 reference statements)
1
21
0
Order By: Relevance
“…In view of these epidemiologic conditions and also of the fact that neither screening of the normal blood donors by particle agglutination nor screening by ELISA resulted in any outright positives, the most likely interpretation of our results is the hypothesis that these weakly reactive antibodies are induced by one or several agents with some structural similarity to HTLV-I. These agents might be normal body proteins, since it has been shown that some MAbs to gag proteins of HTLV-l may also react with antigen of normal thymus (Haynes et al, 1983), or human placenta (Suni et al, 1984). However, it is more likely that the antibodies reacting to more than one of the final gag proteins might have been induced by an infectious agent, possibly a retrovirus distantly related to HTLV -1.…”
Section: Discussionmentioning
confidence: 74%
“…In view of these epidemiologic conditions and also of the fact that neither screening of the normal blood donors by particle agglutination nor screening by ELISA resulted in any outright positives, the most likely interpretation of our results is the hypothesis that these weakly reactive antibodies are induced by one or several agents with some structural similarity to HTLV-I. These agents might be normal body proteins, since it has been shown that some MAbs to gag proteins of HTLV-l may also react with antigen of normal thymus (Haynes et al, 1983), or human placenta (Suni et al, 1984). However, it is more likely that the antibodies reacting to more than one of the final gag proteins might have been induced by an infectious agent, possibly a retrovirus distantly related to HTLV -1.…”
Section: Discussionmentioning
confidence: 74%
“…The anti-p19 MoAb was shown to react with p19 in HUT 102, and with p19 and p28 in MT-2 as previously mentioned (40,41). Anti-p19 MoAbs from some clones were shown to react with, in addition to p19, normal thymic epithelial cells and some of the embryonal cells (7,27,38).…”
Section: Discussion On the Location Of Htlv I Antigensmentioning
confidence: 92%
“…(3) The decre ment of the serum HTLV-I-Ab after thymectomy may, although tentative, raise the intriguing issue of a possible thymic involvement in regulating serum HTLV-I-Ab pro duction. (4) Although the iinmunohistological reaction of the thymic reticular cells may represent a cross-reaction of anti p i 9 antibody to a host protein as Haynes et al [17] reported, they also suggested that antigenicity induced in host T cells by HTLV-I infection may be coexpressed on normal thymic reticular cells. Existence in the present patient, and absence in the controls, of antigenicity for HTLV-I p 19 in thymic reticular cells might connote a pos sible involvement in HTLV-1 infection of thymic reticular cells, and, furthermore, of the interactions of these cells with thymocytes in the regulation of antibody production [ 18].…”
Section: Introductionmentioning
confidence: 99%